Foucault, the Family and Politics
XIII, 243 p.
Keywords: Drawing on the writings of Foucault, this book explores the politics and power-dynamics of family life, examining how everyday obligations such as attending school, going to work and staying healthy are organized through the family. The book includes an essay by Foucault, Les désordres des familles , translated here in English for the first time.